A SCOPE REVIEW ON THE IMPLEMENTATION OF REMOTE TEACHING FOR ENGINEERING LABORATORY COURSES DURING THE PANDEMIC COVID-19 - Mohd Azuan Tukiar; Nor Fauzian Kassim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article aims to carry out a scoping review of the implementation of remote teaching for engineering laboratory courses in higher learning institutions during the pandemic COVID-19. Outcome-Based Education (OBE) implementation has required the graduate to attain a minimum of twelve skills and attributes upon graduating from the engineering program; it includes the psychomotor skill involved in laboratory courses. The finding shows that it has various implementations in conducting laboratory courses during the pandemic. The implementation includes recording a video, conducting an online simulation to replace the experimental work, and transforming face-to-face activity into a virtual lecture, modelling, and simulation. The approach for the laboratory that uses software also has recorded videos, using open-source software similar to the software listed in the syllabus, and some institutions allow students to access the computers lab remotely. There are no physical experimental works carried out in the laboratory during the pandemic due to non-access to the lab. Students then are expected to learn from the video to grasp the knowledge and concept. This ’scope review’ also found that they have not discussed the suitable assessment in evaluating the psychomotor skill during the pandemic. Therefore, this paper recommends conducting a study to determine the implementation of a laboratory course and investigate the effectiveness of the assessment conduct during the pandemic COVID-19 to obtain the course learning outcome and evaluate its psychomotor skill.